Pengolahan Singkong Menjadi Brownies Untuk Meningkatkan Nilai Jual Singkong di Desa Tegalharjo Kecamatan Glenmore Kabupaten Banyuwangi - Siti Aimah; Nawal Ika Susanti; Lely Ana Ferawati Ekaningsih (IAI Darussalam, 2020)
Tegalharjo village is a village in Glenmore sub-district, Banyuwangi district, which has a very large plantation area with a variety of plants. One of the plants that thrives on plantations and people's homes is the cassava tree. But the use of cassava as a village's potential to improve the economy of citizens is less than optimal. Cassava is generally left to rot in the trees, sometimes sold cheaply with a maximum price of Rp 3.000.00 a kilo gram and even ironically it is only used as animal feed. Meanwhile the majority of housewives only depend on the family economy for their husbands' work as farmers, farm laborers, very few who are self-employed and plantation labour majority. Seeing this, there needs to be innovations that can increase the economic value of cassava. One of them by processing cassava into brownies. After being processed into brownies, the selling value automatically increases from a kilo of Rp 3.000,00 to Rp 10,000.00 in a package. This innovation was carried out by the service team through mentoring activities and training in making Brownies of Cassava.